REPRESENTASI ROMANTISME DALAM NOVEL DILAN DIA ADALAH DILANKU TAHUN 1990 KARYA PIDI BAIQ - Rizal, Sinta Aldela; Yesicha, Chelsy (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Romanticism is an overflow of feelings that reflects emotions, the language of love, affection, intimacy of one's feelings to a partner. Romanticism is not only about affection and love, in other words, romanticism is not only beautiful or sweet, but hatred, anger, annoyance, jealousy, selfishness are also included in the category of romanticism. . Romanticism is also very much related to the times and lifestyle of teenagers and students today. Especially for those who live in big cities, this romantic activity is very possible. In fact, because it has often happened, people in big cities consider it normal. Dilan Dia adalah Dilanku Tahun 1990, there are parts of the story that contain romance, but it is packaged in a language that is typical of young people in the 1990s. For this reason, researchers are interested in conducting research to see the romantic representation in novel. Thid writing method is qualitative using naratif analysis Tzvetan Todorov. The subjek of this research is the Dilan Dia adalah Dilanku Tahun 1990 novel by Pidi Baiq. This research focuses on problems related to romantic aspects. The way of data collection is done by documentation and literature study techniques. After collecting data, an analysis of the method of this research was conducted to obtain results. The results of this study indicate that most of the beginning, middle and end of the story in this novel show that romance in this novel is mostly done by Dilan. In this Dilan 1990 novel, the representation of the aspect of romance is more dominant. The aspect of love shown by Dilan to Milea contains more love. Representation of aspects of romance that often arise include love, liking and various expressions of feelings that are often shown by the main characters, Dilan and Milea. However, different from the aspect of expression, only a few parts of the chapter are in the story in the novel Dilan 1990. Representation of aspects of expressions that often appear in the storyline, such as emotions, joys and sorrows, and uncontrollable desires.Â Keywords: Romanticism, Representation, Naratif Analysis